“Miss, I want minum!” How Indonesian Preschool Teachers Perceive Translanguaging Practices in the Classroom - Sitorus, Iriyanti Elphintina; Sahiruddin; Emaliana, Ive (Fakultas Ilmu Budaya, Universitas Brawijaya, 2026)
Over the past decade, translanguaging practices have gained attention in EFL research, especially in promoting multilingual proficiency. While much focus has been on intermediate and advanced learners, there has been less study on early learners, particularly in preschool classrooms. This study aims to answer two questions: 1) How do preschool teachers use translanguaging in an EMI classroom? 2) What strategies do they use to promote it in a multilingual setting? Using a descriptive qualitative approach with observations and interviews, the study involved two teachers from diverse backgrounds in an international preschool. The findings suggest translanguaging fosters inclusivity, deeper language comprehension, and cultural awareness. Despite challenges, the study offers valuable insights into its cognitive, cultural, and linguistic benefits for multilingual children. It calls for further research on the impact of translanguaging beyond the classroom, including interviews with students and parents.